Outpatient management of febrile neutropenia in children with cancer - Ottavio Ziino; Fabio Tucci; Mario Renato Rossi (MDPI AG, 2011)
Optimizing therapeutic strategies based on randomized treatment-comparison studies led to a better prognosis of nearly all pediatric malignancies in the past four decades. While morbidity and mortality of the malignancy itself have been reduced, infections, with or without severe neutropenia, remain the most frequent potentially lethal complications of therapy (1).